Active Offer - A culture of respect, a culture of excellence - Commissariat aux langues officielles (2017)

Clear communication in health care - we all win (long) - A business Case for Quality French-Language Health Care; Translation-Interpretation and Navigation Services as Transitional Solutions - Gauthier, Hubert (2016)

Clear communication in health care - we all win (short) - A business Case for Quality French-Language Health Care; Translation-Interpretation and Navigation Services as Transitional Solutions - Gauthier, Hubert (Conseil Gestion, pour Les réseaux santé – Partenariat Communauté en santé du Yukon et le Réseau Santé en Français de Terre-Neuve-et-Labrador, 2016)

Cadre de référence pour la formation à l’offre active des services de santé en français (n°978-0-9879240-1-8) - Lortie, Lise; Lalonde, André. J. (Consortium national de formation en santé, 2012)

Reference framework: Training for active offer of French-language health services - Lortie, Lise; Lalonde, André. J. (Consortium national de formation en santé, 2012)

Welsh in the health service: The scope, nature and adequacy of Welsh language provision in the National Health Service in Wales. Consumer Council Wales. - Misell, Andrew (2000)
The Welsh Consumer Council set about defining the consumer interest in language in its 1996 report, Welsh as a Consumer Issue. That report emphasised how and why the opportunities for using the Welsh language be considered from the view of the consumer. In general, service providers are well equipped to look after their own interests – the consumer by comparison is often weak. It is this theme that is picked up in this report – Welsh in the Health Service: The Scope, Nature and Adequacy of Welsh Language Provision in the National Health Service in Wales. While the report recognises that, in many instances, Welsh language service provision is about providing equal opportunities and ensuring a high quality, consumer sensitive service, it also identifies groups for whom service provision in the first language is a clinical necessity. The report concludes that in the case of Welsh-speaking patients, there are instances when they cannot be treated effectively except in their first language, or in both their languages. This is especially true in the case of those receiving speech and language therapy, and for the following key groups: - people with mental health problems. - people with learning disabilities and other special needs. - older people, and - young children. The report contains many recommendations and calls for a fundamental change of approach on the part of the NHS in Wales.

« Bâtir sur les fondations - améliorer les résultats pour la santé et accroître la vitalité des communautés anglophones du Québec ». Rapport présenté au ministre fédéral de la santé - Nouvet, Marcel; Maldoff, Eric (Comité consultatif des communautés anglophones en situation minoritaire, 2007)

“Building on the foundations, working toward better health outcomes and improved vitality of Quebec's English-speaking communities”. Report to the Federal Minister of Health - Nouvet, Marcel; Maldoff, Eric (Consultative Commitee for English-Speaking Minority Communities, 2007)

HR Support Kit – Pathway to Bilingual services - Regroupement des intervenantes et intervenants francophones en santé et en services sociaux de l'Ontario (2012)

Trousse d’appui RH – Vers un service bilingue - Regroupement des intervenantes et intervenants francophones en santé et en services sociaux de l'Ontario (2012)

Services en français dans les CLOSM : produire des données probantes pour améliorer l’accès et la qualité. Mémoire du Réseau des services de santé en français de l’Est de l’Ontario dans le cadre de la consultation sur le renouvellement du PCLOS 2013-2018 - Réseau des services de santé en français de l’Est de l’Ontario (2016)

Améliorer l’état de santé des francophones de Terre Neuve-et-Labrador - Réseau Santé en français de Terre-Neuve-et-Labrador (2021)

Working together to implement the Active offer of French-language Services - Particpants's guide - Santé en français (2016)